The Handmaid's Tale [Príbeh služobníčky po anglicky] - Atwood, Margaret, 1939- (Anchor Books, a division of Penguin Random House LLC, 2017)
This look at the near future presents the story of Offred, a Handmaid in the Republic of Gilead, once the United States, an oppressive world where women are no longer allowed to read and are valued only as long as they are viable for reproduction.